Perception of guardians and students of elementary school in Bambuí, MG about remote studies in a period of social distance in Brazil (Research, Society and Development, 2020)
The social distance measures adopted after the beginning of the COVID-19 pandemic had major impacts on education. The replacement of face-to-face teaching with methodologies that rely on the support of information and communication technologies was necessary to maintain educational activities remotely. However, innumerable difficulties were found for the rapid adaptation of schools, teachers, parents or guardians and students to this new reality. The importance of digital inclusion has become even more evident, and the effects on students' learning and mental health can have long-term consequences. This study aimed to obtain more information about the perception of parents and students of elementary schools in the city of Bambuí, MG, regarding non-classroom educational activities carried out during a period of social distance. 54 virtual questionnaires were applied, and it was found that students have cell phones as the main means of accessing the internet. The limitation on internet access was also a listed aspect. Another factor that stood out was the difficulty of students' concentration during the activities. In addition, a significant portion of students are unmotivated and showed symptoms of anxiety during the period of social distance. It is therefore concluded that the social distance has negatively impacted the lives of elementary school students according to the perception of those guardians and of the students themselves, with educational and socio-emotional reflexes.